2010
DOI: 10.3844/ajassp.2010.44.50
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Methionine and Threonine Supplementations on Immune Responses of Broiler Chickens Challenged with Infectious Bursal Disease

Abstract: Problem statement:The aim of this study was conducted to determine the effects of supplementing methionine and threonine higher than the National Research Council (NRC) recommendation in the diets on immune responses of broiler chickens challenged with Infectious Bursal Disease (IBD). Approach: A total of 450 day-old male broiler chicks were assigned to one of the nine dietary treatments. Three levels of methionine (NRC (M1), 2 times NRC (M2) and 3 times NRC (M3)) and 3 levels of threonine (NRC (T1), 2 times N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…Different levels of DEB (Borges, ; Borges et al, ; Ahmad et al., ) as well as SAA (Weissman et al., ; Maroufyan et al., ) when administered individually have remarkable effects on performance and immunological parameters. Investigation of their interactions for additive or reductive effects with respect to the above‐mentioned parameters should be interesting because manipulations in DEB have been shown to affect the metabolic pathway and the fate of some amino acids such as lysine and leucine (Adekunmisi and Robbins, ,b; Brake et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different levels of DEB (Borges, ; Borges et al, ; Ahmad et al., ) as well as SAA (Weissman et al., ; Maroufyan et al., ) when administered individually have remarkable effects on performance and immunological parameters. Investigation of their interactions for additive or reductive effects with respect to the above‐mentioned parameters should be interesting because manipulations in DEB have been shown to affect the metabolic pathway and the fate of some amino acids such as lysine and leucine (Adekunmisi and Robbins, ,b; Brake et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…DEB (Borges, ; Borges et al., ; Ahmad et al., ) or Met (Weissman et al., ; Maroufyan et al., ) each has its own remarkable effects on the performance and immunological responses of birds. The interactions between these two factors could, therefore, be of great interest because of the possible reciprocal relationship(s) between DEB and amino acid metabolism (Patience et al., ; Brake et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, taking threonine into the feed formulation matrix would be a critical limitation in order to use of other EAAs such as total suphur AAs and Lys in the body efficiently (Kidd 2000). Some researcher have shown that excess dietary threonine promoted broiler chicken performance (Rezaeipour et al 2012), immunological responses through increasing the relative weight of immune organs, synthesis of immunoglobulin A (IgA), immunoglobulin G (IgG), and secretory IgA (Corzo et al 2007;Maroufyan et al 2010;Ren et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, the high levels of methionine and cysteine compensates for the tryptophan deficiency. Chicks grown on feed rich in these amino acids (in the absence of tryptophan) were shown to develop resistance to the infectious form of Bursal Disease, thereby compensating for the lack in tryptophan (Maroufyan et al, 2010).…”
Section: Resultsmentioning
confidence: 99%